The Role of Electrode Placement in Bilateral Simultaneously Cochlear-Implanted Adult Patients. (September 2016) - De Seta, Daniele; Nguyen, Yann; Bonnard, Damien; Ferrary, Evelyne; Godey, Benoit; Bakhos, David; Mondain, Michel; Deguine, Olivier; Sterkers, Olivier; Bernardeschi, Daniele; Mosnier, Isabelle
Objective: To evaluate the influence of the electrode placement on hearing performance in adult patients who were simultaneously and bilaterally cochlear implanted. Study Design: Case series with planned data collection. Setting: Tertiary referral university centers. Subjects and Methods: The postoperative computed tomography scan was studied for 19 patients who were simultaneously and bilaterally implanted with a long straight electrode array. The size of the cochlea was measured in consideration of the major cochlear diameter and cochlear height. The electrode-to-modiolus distance for the electrodes positioned at 180 and 360 degrees and the angular depth of insertion of the array were also measured. Speech perception was assessed at 1 and 5 years postimplantation with disyllabic word lists in quiet and in noise, with the speech coming from the front and a background noise (cocktail party) coming from 5 loudspeakers. Results: At 1 year postimplantation, the electrode-to-modiolus distance at 180 degrees was correlated with the speech perception scores in both quiet and noise. In patients with a full electrode insertion, no correlation was found between the angular depth of insertion and hearing performance. The speech perception scores in noise gradually declined as a function of the number of inserted and active electrodes. No relationship between electrode position and speech perception scores was found at 5 years postimplantation. Conclusion: In adult patients who were simultaneously and bilaterally implanted, the use of a long straight array, the full electrode array insertion, and the proximity to the modiolus might be determining factors to obtain the best speech performance at 1 year, without influence on the speech perception scores after long-term use.